Alamat ni China Doll - Diaz, Lav
Helen lives with her grandmother in an idyllic island down South. At 27, she is about to graduate from high school and start a new life. Things take a drastic turn when journalist Perry Nanali's article on the truth about "China Doll" is exposed. Now, she is haunted by her past that she tried to forget.--anonymous